Penentuan Peringkat Penilaian Kinerja Pegawai Sebagai Pendukung Keputusan Menggunakan Metode Fuzzy Elimination Et Choix Traduisant La Realite - Rika Dina Amalia, Dina Amalia; Alisah, Evawati; Juhari, Juhari (Jurnal Riset Mahasiswa Matematika, 2023)
This study discusses the Fuzzy Elimination Et Choix Traduisant La Realite (ELECTRE) method that can be applied to make a decision support. This method was chosen because it is one of the methods used to rank and determine the best alternative. This study aims to determine the results of the application of the fuzzy ELECTRE method which produces alternative solutions in determining employee performance appraisal ratings for the Education and Culture Office of Malang City. Some of the problems that often occur in employee performance evaluation at the Department of Education and Culture in the city of Malang are still ineffective and inaccurate because the calculation process is still manual. Based on this, the effort to reduce the problems above is to implement a Fuzzy Multi Attribute Decision Making decision support system with the fuzzy ELECTRE method. This method requires a process of normalizing the decision matrix (X) into a comparable scale, then weighting the normalized matrix, then determining the concordance and discordance indices for each alternative pair to calculate the concordance and discordance indices, the ranking process is used to choose the best alternative. This study is limited by several criteria used as linguistic variables with the Triangular Fuzzy Number scale, including SKP scores, service orientation, integrity, commitment, discipline, and cooperation. Based on employee performance appraisal data that has been calculated using the fuzzy ELECTRE method, the best alternative that occupies the top rank with the highest value is alternative 2 with a value of 55.9155. It is hoped that by using the fuzzy ELECTRE method, the ranking process can be more precise in identifying employees who will become outstanding employees.